Sociabilities and permeable realities - Gosciola, Vicente (FCL-UNESP Laboratório Editorial, 2008)
This paper aims to conceptualize Permeable Realities as the combination process between sociability and pervasive computing. The text deals with sociability procedures and effects that happen in collaborative media which have used communication technological resources. It compares the way sociability is organized throughout the communication history to the current social changes determined by technological innovations and by the collaborative networks.